Effect of nano Al2O3 coated Ag reinforced Cu matrix nanocomposites on mechanical and tribological behavior synthesis by P/M technique. (December 2020) - Mohamed, A; Mohammed, MM; Ibrahim, AF; El-Kady, Omyma A
In this study, copper powder was reinforced with different weight percentages of Al2 O3 particles (0, 5, 10, and 15 wt.% Al2 O3 coated Ag) to produce Cu-Al2 O3 composites by mechanical alloying and uniaxial cold pressing/sintering route. Electro-less deposition was used to coat Al2 O3 particles with Ag. The microstructure of the consolidated samples was investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX) elemental mapping. The porosity, microhardness, and wear behavior of the consolidated samples were also investigated as a function of Al2 O3 content. The EDX mapping images reveal that the Al2 O3 reinforcement particles were homogeneously distributed into the Cu matrix. Microstructural analysis shows that the addition of Al2 O3 coated Ag particles improves density of the composites coating. SEM micrographs result shows that slight porosities exist in the composites produced. Furthermore, the average hardness of the composite coatings varies from 72.3 to 187.6 HV as Al2 O3 content increases from 0 to 15 wt.%. The wear test results showed that the composite with higher Al2 O3 content 15 wt.% showed the best wear resistance.